2017
DOI: 10.15835/nsb9310123
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nutrient Contents of Soil across Different Land Uses in a Forest Reserve

Abstract: In order to assess the changes in soil chemical properties' resulting from conversion of forest to other agricultural land uses a study was conducted in Okomu Forest Reserve (Nigeria). Five soil samples collected from top and sub soils of marked points within the undisturbed forest, farmland, cocoa plantation, oil palm plantation and rubber plantation were analyzed for pH, organic carbon, total nitrogen, available phosphorus, exchangeable acidity, sodium, potassium, calcium and magnesium. The results showed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Henril et al (2020) reported that the use of forest reserves for other land usage has resulted into sundry and multifarious ecological problems. Soil physical and chemical properties have been used by many researchers for assessing the influence of land-use on changes and management of the ecosystem (Mitchel et al, 2010;Agboola et al, 2017;Akintola et al 2020a andb, Akintola et al 2021). The management of soil and the maintenance of its quality depend widely on frequent evaluating of soil properties to farming, cultivation and other land use (Chima et al, 2009)) Thus, it is paramount to understand the effects of land use types on soil properties for environmental sustainability and management.…”
mentioning
confidence: 99%
“…Henril et al (2020) reported that the use of forest reserves for other land usage has resulted into sundry and multifarious ecological problems. Soil physical and chemical properties have been used by many researchers for assessing the influence of land-use on changes and management of the ecosystem (Mitchel et al, 2010;Agboola et al, 2017;Akintola et al 2020a andb, Akintola et al 2021). The management of soil and the maintenance of its quality depend widely on frequent evaluating of soil properties to farming, cultivation and other land use (Chima et al, 2009)) Thus, it is paramount to understand the effects of land use types on soil properties for environmental sustainability and management.…”
mentioning
confidence: 99%